Fabrication of electrospun polyacrylonitrile ion-exchange membranes for application in lysozyme adsorption (eXPRESS Polymer Letters, 2011)
Ion exchange (IEX) chromatography is commonly used in separation and purification systems. However, micropore blockage within its resin structure can easily lead to a reduction in the effectiveness of purification. To tackle this problem, we adopted the concept of membrane separation by combining electrospinning techniques with rapid alkaline hydrolysis to prepare a weak acid IEX nanofibrous membrane (AEA-COOH), consisting of polyethyleneterephthalate (PET) meltblown fabric as a supporting layer, with upper and lower IEX layers consisting of polyacrylonitrile (PAN) nanofibrous membranes. To determine the characteristics of the AEA-COOH membrane, we used the commercial product Sartobind© C IEX membrane as the standard of comparison. Results showed that the base weight and thickness of AEACOOH were 33 and 64%, relative to Sartobind© C membrane. The thermo-degradable temperature of AEA-COOH membrane (320°C) was far higher than that of Sartobind© C (115°C), indicating high thermal stability. Finally, comparisons between the lysozyme adsorption rates and capacity of various IEX membranes confirmed that AEA-COOH was lighter, thinner, faster, possessing higher protein adsorption efficiency than Sartobind© C membrane.